2006
DOI: 10.1590/s1519-566x2006000400016
|View full text |Cite
|
Sign up to set email alerts
|

Diversidade e sazonalidade de ácaros (Acari) em seringal (Hevea brasiliensis, Muell. Arg.) no Noroeste do Estado de São Paulo

Abstract: Diversity and Seasonal Occurrence of Mites (Acari) in a Rubber Tree Crop (Hevea brasiliensis, Muell. Arg.) in Northwestern São Paulo, Brazil ABSTRACT -Brazilian southeastern region has soil and climate conditions suitable for the growing of rubber trees, and most part of national yield arises from São Paulo State. The aims proposed for this work were to determine the diversity, the richness and the seasonal occurrence of mites found in a rubber tree crop in a triennial survey with monthly samplings, as well … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
32
0
26

Year Published

2006
2006
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(63 citation statements)
references
References 18 publications
5
32
0
26
Order By: Relevance
“…After the year 2000, T. heveae was reported a number of times as a pest of rubber trees (Pontier et al, 2000;Ferla and Moraes, 2002;Hernandes and Feres 2006a, b;Vis et al, 2006;Daud and Feres, 2007). In São Paulo, T. heveae is usually very numerous (Feres et al, 2002;Bellini et al, 2005;Hernandes and Feres, 2006a;Vis et al, 2006). This species inhabits mainly the abaxial surface of leaves and causes bronzing followed by premature leaf drop (Moraes and Flechtmann, 2008).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…After the year 2000, T. heveae was reported a number of times as a pest of rubber trees (Pontier et al, 2000;Ferla and Moraes, 2002;Hernandes and Feres 2006a, b;Vis et al, 2006;Daud and Feres, 2007). In São Paulo, T. heveae is usually very numerous (Feres et al, 2002;Bellini et al, 2005;Hernandes and Feres, 2006a;Vis et al, 2006). This species inhabits mainly the abaxial surface of leaves and causes bronzing followed by premature leaf drop (Moraes and Flechtmann, 2008).…”
Section: Resultsmentioning
confidence: 99%
“…It has therefore received increasing attention in recent decades, given that its usual cultivation over extended areas as a monocrop favours the appearance of pest species. This makes it highly important to study the mite fauna of rubber crops (Feres, 2000;Hernandes and Feres, 2006a). Studies of this nature may lead to the discovery of potential pest species and also their natural enemies, generating data to support the development of integrated pest management programmes specifically designed for rubber tree plantations (Hernandes and Feres, 2006a).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Esses ácaros têm sido registrados na cultura em elevados níveis populacionais, principalmente no período de fevereiro a junho (Vieira & Gomes, 1999;Hernandes & Feres, 2006;Vis et al, 2006). O ataque das duas espécies provoca amarelecimento progressivo das folhas e posteriormente o desfolhamento das plantas (Vieira & Gomes, 2003) antes do período normal de senescência.…”
Section: Introductionunclassified
“…This species goes through two nymphal stages before reaching adulthood, and the females had mean life expectancy of 28.5 days when reared on the clone PB 260 . Feres et al (2002), Bellini et al (2005), Hernandes & Feres (2006a) and Vis et al (2006), reported T. heveae as one the most abundant phytophagous mites on rubber tree crops in São Paulo State. Heavy infestations have also been registered (J. F. C. Benesi pers.…”
mentioning
confidence: 99%